An Experimental Study of the Unbalance Compensation by Voltage Source Inverter Based STATCOM - Anas Benslimane; Jamal Bouchnaif; Mohamed Azizi; Khalid Grari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This work presents an experimental study of the unbalance compensation caused by the high speed railway substations in the high-voltage power grid with a shunt voltage source inverter based STATCOM. This experimental study is realized on a reduced scale prototype. The Control of inverter is implemented in a DSP card. The practical results presented in this paper are shown the performance of unbalance compensation by VSI_STATCOM in static and dynamic regime.